Komodifikasi Konten Media Penyiaran: Relasi Politik pada Program Media MNCTV (Lintas iNews) - Iffa Auliya; Inki Azir; Intan Tri Utami; Muhammad Thoriq Aziz; Pia Khoirotun Nisa (MUKASI: Jurnal Ilmu Komunikasi, 2024)
Media is a public means that functions to fulfill society's need for information and is a pillar of democracy. However, in the industrial structure, media is no longer seen based on its use value. but focuses on the exchange rate in obtaining economic benefits. The media and press, as the 4th pillar of democracy and a tool of social control, continue to have their independence stripped away by economic and political interests. The aim of this research is to determine the power relations and dynamics of media content in the study of the political economy of media on MNCTV in the cross i-news program. The research method uses a qualitative descriptive research type using an approach to political economy studies. Primary data collection techniques through literature study regarding MNCTV data on cross-i-News programs, and secondary data through observation and literature on MNCTV. The results of this research can be concluded that MNCTV as a media corporation cannot avoid intervention by the interests of capital and power owners. Political Economy and Power Relations are two things that a media corporation like MNCTV must continue to play correctly in order to continue to win the competition between media.